Improvements of electromechanical properties of gelatin hydrogels by blending with nanowire polypyrrole: Effects of electric field and temperature - Tungkavet T. (2014)
Nanowire-polypyrrole/gelatin hydrogels were fabricated by dispersion of nanowire-polypyrrole into a gelatin aqueous solution followed by solvent casting. The electromechanical properties, thermal properties and deflection of pure gelatin hydrogel and nanowire-polypyrrole/gelatin hydrogels were studied as functions of temperature, frequency and electric field strength. The 0.01%, 0.1%, 0.5%, 1% v/v nanowire-polypyrrole/gelatin hydrogels and pure gelatin hydrogel possess storage modulus sensitivity values of 0.75, 1.04, 0.88, 0.99 and 0.46, respectively, at an electric field strength of 800 V mm -1. The effect of temperature on the electromechanical properties of the pure gelatin hydrogel and nanowire-polypyrrole/gelatin hydrogels was investigated between 30 and 80 °C; there are three regimes for the storage modulus behaviour. In deflection testing in a cantilever fixture, the dielectrophoresis force was determined and found to increase monotonically with electric field strength. The pure gelatin hydrogel shows the highest deflection angle and dielectrophoresis force at an electric field strength of 800 V mm -1 relative to those of the nanowire-polypyrrole/gelatin hydrogels. © 2012 Society of Chemical Industry.